Effect of ultraviolet radiation on clearance rate of planktonic copepods with different photoprotective strategies. Issue 1 (20th March 2019) - Laspoumaderes, Cecilia; Bastidas Navarro, Marcela; Souza, María S.; Modenutti, Beatriz; Balseiro, Esteban
Abstract: We studied two populations of Boeckella gracilipes and two populations of Boeckella gibbosa that inhabit mountain lakes from North‐Patagonian Andes with different optical properties. We combined field and laboratory experiments to determine the effects of ultraviolet radiation (UVR) on clearance rate among these taxa that had different UVR defences. The copepod populations differed in photoprotective compounds (carotenoids and mycosporine‐like amino acids [MAAs]) and antioxidant enzymes (glutathione S‐transferase [GST]). These variations were related to elevation, dissolved organic carbon content and the optical features of the inhabited lakes. Laboratory experiments showed a decrease in the clearance rate (CR) in all populations exposed to UVR. Consistently, the long‐term field experiment showed a negative impact of UVR on CR. We conclude that UVR exposure affects feeding, however, the magnitude of this negative effect depends on the exposure intensity and the photoprotective mechanisms used by zooplankton.